PEMANFAATAN LAHAN TIDAK PODUKTIF DI DESA PESANGGRAHAN BATU UNTUK BUDIDAYA MELON DAN KALE MENGGUNAKAN METODE HIDROPONIK RAKIT APUNG (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Pesanggrahan Village is one of the villages located in Batu District, Batu City. Geographically, this village is located on the slopes of Mount Pesanggrahan. The residents of this village have their main livelihoods as cattle breeders and vegetable farmers. The vegetables that are often planted are chilies, tomatoes, mustard greens, lettuce, spring onions, eggplants, and cucumbers. The method used to plant these vegetables is still traditional, namely by planting directly in the soil or plantation land. This community service activity was carried out based on situation analysis and discussions with the RT head and the PKK mothers' group of Pesanggrahan Batu village. This activity aims to overcome various problems such as unproductive land, low income of PKK mothers' families, lack of knowledge of hydroponic plant cultivation, and knowledge of post-harvest fruit handling and marketing. This activity involved 14 KKN students to utilize idle land in the Pesanggrahan Batu area in order to produce vegetable products that are beneficial to the local community. so that the requirements for clean water have been met.